Religion, pilgrimage, and tourism : critical concepts in religious studies - Norman, Alex; Cusack, Carole M. (Critical concepts in religious studies, 2015)
"For as long as human beings have existed they have been interested in travel. Their homelands and cultural norms have always been constructed with reference to, or contrasted with, the lands and habits of 'the Other'. Implicit in this statement is the notion that some places are more special (perhaps sacred) than others, and this is the core of the intimate relationship between human beings, place and travel, and religion"--